Diversity of Bird Species in Training and Model Forest of Faculty of Forestry Science, National University of Laos A case study of Napo Village, Sangthong District, Vientiane Capital - Ackhavong, Somsanook; PHENGVICHITH, Vansaleum; SAYYAVONG, Kamdet; SITTHIVONG, Kiphet; KUTTIYALAD, Autsaphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research are the objectives to study the diversity of bird species in 3 different forest areas: forest plantation area, agricultural land and natural forest area. Which the tools used in the study are the interviews with people who found types of bird species in the area and direct survey belong point transects or point count with take note and then analyzed by formula frequency ratio and dominant ratio. From the interview, there are 53 species of birds, 43 genus and 9 orders in the study area as forest plantation area of 30 species, 24 genus, 6 orders, agricultural land area of 31 species, 24 genus, 9 orders, and nature forest area of 12 species, 10 genus, 3 orders. From the actual survey in 3 areas it was found that there are 49 bird species, 37 genus and 11 orders. Species were not found in the survey but found in the interview of 17 species, 16 genus, 7 orders, and species found outside of the interview of 15 species, 14 genus, 6 orders. In that there are 2 species in the prohibited category of poultry or his list 1, namely: the Nokkotpeut (Centropus sinensis), and the KaiKuaNin (Lophura diardi), but from the actual survey it was found only by the NokkotPeut (Centropus sinensis), As for the KaiKuaNin (Lophura diardi) is not found, Status by Threatened Species List of IUCN and aquatic and wildlife list of Laos: 7 species and 1 species on the list (1) of 2008 aquatic and wildlife.